Application of Lecture and Group Discussion Methods in Efforts to Increase Students' Understanding of Aqidah and Moral Subjects at MTs Aisyiyah, Binjai City - Nabila Syafinka Putri (AR-RASYID : Jurnal Pendidikan Agama Islam, 2023)
Learning is a process activity carried out by individuals with the aim of obtaining a change in behavior as a form of experience in their interaction with the environment. This research was carried out with the aim of improving learning outcomes in the subject of moral aqidah at MTs Aisyiyah through direct implementation using lecture and group discussion methods. The subjects in this research were teachers who applied the discussion and lecture learning model. The research method used was qualitative and observational. The data generated from this research comes from teachers of the Aqidah akhlak subject who were interviewed and observations made at MTs Aisyiyah. The data analysis techniques used in this research are data reduction, data presentation, verification and conclusions.